PELAKSANAAN BELAJAR DARI RUMAH (BDR) SECARA ONLINE SELAMA DARURAT COVID-19 DI SMP N 1 SEMIN - Susi Prasetyaningtyas (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
The spread of the Corona virus that causes Covid-19 disease led the government issuing a new policy in the field of education. The policy aimed to prevent the Corona virus spread within the educational unit. The policy adopted was the Online School from Home (SFH) implementation. Online learning used smart phones through the Internet network. SFH online has been implemented for the first time in SMP N 1 Semin. Many obstacles occurred during the implementation of SFH, among others: unstable internet connection or network, internet data and limited facilities of android smart phones. The survey results from the students stated that there were things that are not pleasant during SFH that are boring, lack of student motivation, too many tasks, lack of focus in learning, and the learning atmosphere is less fun. Ninety percent of students wanted to go back to school and interacted with schoolmates. The implementation of the SFH continued to be extended until the education environment is safe for teaching and learning. Schools were trying to implement strategies so that SFH runs well. This strategy was a joint discussion between the school and the school committee, adjusting the SFH school schedule, and implemented IT training for teachers.